Innovation in Physician Remuneration in France: What Lessons for Canada? - Marie-Pascale Pomey; Jean-Louis Denis; Mélina Bernier; Simon Vergnaud; Johanne Préval; Olivier Saint-Lary (McMaster University Library Press, 2019)
During the past decade, France has experienced two major reforms in remuneration models for general practitioners who work outside public healthcare organizations: Remuneration for Public Health Objectives (Rémunération sur Objectifs de Santé Publique-ROSP) and Experiments with New Models of Remuneration (Expérimentations desNouveaux Modes de Rémunération-ENMR). These two initiatives introduced payments based on performance in the areas of quality of care, organization of services and multidisciplinary practice. In the first model, individual physicians receive incentives for preventive practices, use of generics and improvements in work organization. In the second model, incentives are provided to multi-professional practice groups to foster interdisciplinary collaboration and patient involvement. While French general practitioners accustomed to fee-for-service remuneration were at first reluctant to accept a mixed remuneration model, they eventually came to embrace it. The ROSP has significantly improved targeted areas of practice, although it has had less impact on preventive practices than on use of generics and work organization. The ENMR has helped formalize inter-professional relationships in primary care and has thus contributed to team integration. These "experiments" suggest that a deliberate distinction between changes to individual physician payment and changes to how multi-professional practice groups are paid and practice may be a good starting point when introducing financial incentives to enable benefits and avoid negative consequences.